Mengulik Longevity : Dinamika Usaha Gen Z yang Berhenti di Tengah Jalan - Putri Fildzatul Jannah; Naili Nuzul Fadila; Rauly Sijabat (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The phenomenon of business termination mid-stream is still widely experienced by Generation Z entrepreneurs, particularly students who run their own businesses. This study aims to explore the dynamics of Gen Z business longevity by analyzing factors influencing business continuity and termination. This study uses a qualitative approach with a grounded theory method to explore the relationships between variables, including passion alignment, entrepreneurial motivation, social support, marketing strategy, time management barriers, operational barriers, the business life cycle, and post-business satisfaction and regret. The results indicate that passion alignment and social support play a significant role in shaping motivation and business resilience, while digital marketing strategies influence the dynamics of business activity. However, limited time management and operational constraints are dominant factors that accelerate business termination. Experience navigating the business cycle shapes learning, satisfaction, and regret, which ultimately influence an individual's intention to continue a business in the future. This study confirms that Gen Z business longevity is dynamic and influenced by the interaction of internal and external factors in the context of student entrepreneurship.